Strategic administration - a case study based on Apple (Research, Society and Development, 2020)
Bearing in mind that in a changing scenario, understanding the totality of a situation, mastering the details and planning can be vital for the survival of a company, research on strategic management - a case study based on Apple, with the objective trying to exhibit the way a company that was supposedly created in a garage, can dictate the rules of the market. Therefore, it is necessary to identify one of the main responsible for the success obtained over the years in the world of technology, to show the importance of strategic management in the midst of a company's ups and downs. Then, a research with qualitative approach and bibliographic review is carried out. Therefore, it appears that assessing opportunities and threats from the external environment is essential for the formulation of strategies and Apple directly related to the generic strategy conceptualized as differentiation. Therefore, it appears that the success of the Apple company is certainly linked to a visionary mind, which thinks differently and takes attitudes with a focus on revolutionary ideas and competitive and mature strategic planning. The person responsible for Apple's success is supposedly Steve Jobs, who always sought to attract great people to do equally great jobs for him. Jobs caused innovations because he understood the totality of a situation and dominated the details, even though he did not believe in an innovation system. Therefore, it is possible to state that achieving success in the business world does not depend only on a good leader, but on a focused team, in search of the same objective and competitive strategic planning.